The Respiratory Chain of Plant Mitochondria: XI. Electron Transport from Succinate to Endogenous Pyridine Nucleotide in Mung Bean Mitochondria - Storey, Bayard T. (1971)
Energy-linked reverse electron transport from succinate to endogenous NAD in tightly coupled mung bean (Phaseolus aureus) mitochondria may be driven by ATP if the two terminal oxidases of these mitochondria are inhibited, or may be driven by the free energy of succinate oxidation. This reaction is specific to the first site of energy conservation of the respiratory chain; it does not occur in the presence of uncoupler. If mung bean mitochondria become anaerobic during oxidation of succinate, their endogenous NAD becomes reduced in the presence of uncoupler, provided that both inorganic phosphate (P(i)) and ATP are present. No reduction occurs in the absence of P(i), even in the presence of ATP added to provide a high phosphate potential. If fluorooxaloacetate is present in the uncoupled, aerobic steady state, no reduction of endogenous NAD occurs on anaerobiosis; this compound is an inhibitor of malate dehydrogenase. This result implies that endogenous NAD is reduced by malate formed from the fumarate generated during succinate oxidation. The source of free energy is most probably the endogenous energy stores in the form of acetyl CoA, or intermediates convertible to acetyl CoA, which removes the oxaloacetate formed from malate, thus driving the reaction towards reduction of NAD. In the absence of P(i) and presence of oligomycin, oxidation of succinate by the alternative cyanide-insensitive oxidase pathway, in the presence of sulfide to inhibit cytochrome oxidase, does not reduce endogenous NAD, either in the aerobic steady state or in anaerobiosis. Under these conditions, only the reversed electron transport pathway from succinate to endogenous NAD is active and ATP cannot interact with the respiratory chain. The source of energy for NAD reduction must come from the respiratory chain, and this result shows that oxidation of succinate through the alternate pathway does not provide this energy.